Pengaruh Pengendalian Internal dan Audit Internal Terhadap Good Corporate Governance (Studi Pada BUMN yang Berkantor Pusat di Bandung) - Anike Putri (Economics Professional in Action (E-Profit), 2020)
The research aims to examine the effect of internal control and internal audit towards good corporate governance. This research was conducted in state-owned companies headquartered in Bandung. The method used in this research is quantitative descriptive method. The data used are primary and secondary data. Primary data sourced from the result of questionnaire responses, while for secondary data sourced from the company's annual report. The data analysis model used is path analysis. Based on the result of statistical test, it concludes that internal control and internal audit both simultaneously and partially has a significant effect towards good corporate governance in state-owned companies headquartered in Bandung.